2011
DOI: 10.1016/j.cell.2011.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Stress-Induced, ATF-2-Dependent Epigenetic Change

Abstract: Atf1, the fission yeast homolog of activation transcription factor-2 (ATF-2), contributes to heterochromatin formation. However, the role of ATF-2 in chromatin assembly in higher organisms remains unknown. This study reveals that Drosophila ATF-2 (dATF-2) is required for heterochromatin assembly, whereas the stress-induced phosphorylation of dATF-2, via Mekk1-p38, disrupts heterochromatin. The dATF-2 protein colocalized with HP1, not only on heterochromatin but also at specific loci in euchromatin. Heat shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
281
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 297 publications
(302 citation statements)
references
References 42 publications
20
281
0
1
Order By: Relevance
“…Epigenetic inheritance has been demonstrated in several species including worm (2), fly (3) and mouse species (4,5). Epigenetic inheritance can be modulated by environmental factors and transmitted to subsequent generations via germline cells (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic inheritance has been demonstrated in several species including worm (2), fly (3) and mouse species (4,5). Epigenetic inheritance can be modulated by environmental factors and transmitted to subsequent generations via germline cells (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from both animals and plants indicate that epigenetic resetting is not always complete and hence that acquired epigenetic states may be transmitted from parents to offspring ('germ-line epigenetic inheritance' or 'incomplete epigenetic resetting' or 'incomplete epigenetic reprogramming'; e.g. [6][7][8][9][10][11][12][13][14] reviewed in [4,5,[15][16][17][18][19]). …”
Section: Introductionmentioning
confidence: 99%
“…140 In D. melanogaster, an osmotic or heat stress stimulus can disrupt the activity of the transcription factor ATF-2 and deposition of the repressive histone modification H3K9me2, and this disruption can be transmitted to the next generation in a non-Mendelian manner. 141 In mice, F1 offspring of males fed a low-protein diet exhibit altered liver gene expression profiles, and F1 female offspring of male rats fed a high-fat diet have impaired glucose tolerance and insulin secretion despite being indistinguishable by genotype. 142,143 One historical cohort study in humans has also suggested a transgenerational effect of paternal nutrition on the metabolic status of children and grandchildren.…”
Section: Inheritance (Box 2)mentioning
confidence: 99%